2014
DOI: 10.3390/ijerph111010036
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Production of Th1/Th2/Th17-Related Cytokines in Serum of C57BL/6 Mice after Short-Term Formaldehyde Exposure

Abstract: Previous studies have shown that formaldehyde (FA) could cause immunotoxicity by changing the number of T lymphocytes and that cytokines play a pivotal role in the regulation of T lymphocytes. However, the previously used cytokine detection methods are difficult to use in the measurement of several cytokines in a small amount of sample for one test. Therefore, the cytometric bead array (CBA) technique was used. CBA showed better analytical efficiency and sensitivity than the previous methods. C57BL/6 mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Briefly, LNCs obtained from mice immunized with PLP 139-151 were stimulated with PLP 139-151 or control (NASE 101-120) with or without DHT or its ethanol. First, we analyzed the cytokine secretion in culture supernatants on day 3 poststimulation using cytokine capture beads to include a panel of Th1, Th2, and Th17 cytokines, in addition to two other inflammatory cytokines, IL-6 and TNF-α (Wei et al, 2014). The data revealed that supernatants obtained from cells stimulated with PLP 139-151 with or without ethanol showed the presence of all the cytokines, in the order from Th1, followed by Th17 and Th2 cytokines, and TNF-α and IL-6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, LNCs obtained from mice immunized with PLP 139-151 were stimulated with PLP 139-151 or control (NASE 101-120) with or without DHT or its ethanol. First, we analyzed the cytokine secretion in culture supernatants on day 3 poststimulation using cytokine capture beads to include a panel of Th1, Th2, and Th17 cytokines, in addition to two other inflammatory cytokines, IL-6 and TNF-α (Wei et al, 2014). The data revealed that supernatants obtained from cells stimulated with PLP 139-151 with or without ethanol showed the presence of all the cytokines, in the order from Th1, followed by Th17 and Th2 cytokines, and TNF-α and IL-6 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IL-2 and IFN-γ are produced by Th1 cells to promote viral clearance by stimulating proliferation and cytotoxic T lymphocyte responses [ 45 ]. IL-4 is involved in a Th2 response, and IL-10 produces an anti-inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Male C57BL/6 mice were housed as previously described [ 55 ]. Normal diets and water were given ad libitum throughout the study period.…”
Section: Methodsmentioning
confidence: 99%